Nanoengineered polyglutamic acid fertilizers via self-assembly for efficient tomato growth - Dong, Jiangtao; Li, Hexin; Yuan, Bowen; Zhang, Donghui; Wang, Hongliang; Wang, Tao; Li, Songwei; Liu, Runqiang (Frontiers in Plant Science, 2026)
IntroductionPolyglutamic acid (γ-PGA) is a promising biostimulant for enhancing crop growth and stress resistance, while its agricultural application is limited by poor leaf retention, low mobility within plants, and susceptibility to rain wash-off.MethodsThis study developed PGA nanofertilizers via a facile one-step self-assembly strategy in crude γ-PGA aqueous solution without adding salt ions to overcome these limitations. SEM images show that the obtained nanoparticles appear uniform spherical morphology and good dispersibility in water with an average hydrodynamic diameter of 182 nm confirmed by DLS. XRD and DSC patterns indicate a strong reduction in crystallinity consistent with a largely amorphous or highly disordered state.ResultsFluorescence imaging of FITC-labeled PGA nanofertilizers (FITC@PGA) indicates systemic, vascular-localized signals consistent with bidirectional movement from absorption of both roots and leaves. Importantly, the PGA nanofertilizers exhibited superior rainfastness and leaf retention compared to crude γ-PGA. Physiological assessments showed that foliar application of PGA nanofertilizers significantly enhanced chlorophyll content, root development, and antioxidant enzyme activities compared to that of crude γ-PGA, which led to significant improvement for tomato growth and stress tolerance.DiscussionIt is clear shown that the nano-engineering strategy will provide a promising approach for developing efficient and eco-friendly nanofertilizer.